2004
DOI: 10.1111/j.1365-2929.2004.01957.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of computer-assisted instruction (CAI) versus traditional textbook methods for training in abdominal examination (Japanese experience)

Abstract: The results suggest that computer-assisted learning methods will be of greater help to students who do not find the traditional methods effective. Explorations of the factors behind this are a matter for future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
2
7

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(84 citation statements)
references
References 22 publications
6
66
2
7
Order By: Relevance
“…THE EFFECTIVENESS OF EARLY CLINICAL EXPOSURE AND E-LEARNING IN TEACHING ANATOMY. result in our studies [15]. Instead, it was noted that high and average achievers performed similarly after e-learning, the method not being able to discriminate between the two groups.…”
Section: Total Scorescontrasting
confidence: 49%
See 1 more Smart Citation
“…THE EFFECTIVENESS OF EARLY CLINICAL EXPOSURE AND E-LEARNING IN TEACHING ANATOMY. result in our studies [15]. Instead, it was noted that high and average achievers performed similarly after e-learning, the method not being able to discriminate between the two groups.…”
Section: Total Scorescontrasting
confidence: 49%
“…A further sub-analysis demonstrated that the CAL package gave the most benefit to the low achievers while high achievers were less affected by the method of instruction [15]. In a randomized controlled trial by Nicholson, the group having access to the computer model of anatomy of internal ear scored Chimmalgi M, Regi Jose, K Chandra Kumari.…”
Section: Total Scoresmentioning
confidence: 99%
“…Most of this research is focused on technology-enhanced classrooms, CAI (computer assisted instruction), elearning interventions, and the like. The achievements of students are seen as a result of the support coming from ICT-aware teachers or school organization (Bell, 2007;Carle, Jaffee, & Miller, 2009;Pedro, 2005;Qayumi et al, 2004;Vernadakis, Antoniou, Giannousi, Zetou, & Kioumourtzoglou, 2011). That this is not always true is confirmed by Svirko and Mellanby (2008).…”
Section: Theoretical Backgroundmentioning
confidence: 86%
“…In the section on the "Theoretical background" it was argued that technology-enhanced classrooms, CAI, e-learning, and the like may have a discernable influence on educational attainment (Carle et al, 2009;Pedro, 2005;Qayumi et al, 2004;Vernadakis et al, 2011), but it has also been demonstrated that the influence is not always positive (Hunley et al, 2005;Şendag & Odabaşi, 2009;Svirko & Mellanby, 2008). In this research we did not investigate CAI or e-learning.…”
Section: Discussionmentioning
confidence: 99%
“…Our own recent search identified eight quantitative studies (Tam 2009) which provided some evidence to support the use of computer-assisted learning specifically in the setting of undergraduate medical anatomy. Identified trials included computerbased teaching for learning anatomy of the inner ear (Nicholson 2006), the carpus (Garg 1999(Garg , 2001(Garg , 2002, surface anatomy of the abdomen (Hallgren 2002;Qayumi 2004) and anatomy and physiology of the biliary tree (Devitt 1999), and in general reported an improvement in knowledge. However, these trials were conducted over short teaching periods and in limited areas of anatomy.…”
Section: Introductionmentioning
confidence: 99%